1985
DOI: 10.1111/j.1651-2227.1985.tb10095.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis precursors in Finnish children and adolescents. XIII. Serum and hair copper and zinc concentrations

Abstract: ABSTRACT. The copper and zinc status of 3–18‐year‐old Finnish children was estimated by analysing 3,480 serum copper and zinc concentrations, 853 hair copper and 868 hair zinc concentrations. Both copper and zinc have been proposed to be connected with the pathogenesis of cardiovascular diseases. In addition, zinc is essential for normal growth and development. The mean serum copper concentration of 3‐year‐old children was 21.2 μmol/l and the concentration was significantly lower in older age groups. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][8][9][10][11][12] An extensive study on zinc and copper in Finland showed the serum zinc level of 3-18 year-old subjects to be 95.2±17.2 µg/dL. 16 In the present study, the serum level was 86.8±19.6 µg/dL, which was lower, although not significantly different from the reference value (100.0±20.0 µg/dL). Also, while the serum zinc and copper levels in girls were lower than in boys in the Finnish study, no sex difference was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][8][9][10][11][12] An extensive study on zinc and copper in Finland showed the serum zinc level of 3-18 year-old subjects to be 95.2±17.2 µg/dL. 16 In the present study, the serum level was 86.8±19.6 µg/dL, which was lower, although not significantly different from the reference value (100.0±20.0 µg/dL). Also, while the serum zinc and copper levels in girls were lower than in boys in the Finnish study, no sex difference was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…S-Zn, S-Cu and anthropometric variables used in this study were determined as part of the Multicentre Study of Atherosclerosis Precursors in Finnish children and adolescents in 1980 (10)(11)(12). The study was carried out in five university cities and in 12 rural communities in their vicinity in different parts of Finland.…”
Section: Methodsmentioning
confidence: 99%
“…S-Zn and S-Cu were determined from morning fasting blood ST, sum of triceps and subscapularis skinfold thicknesses samples collected in acid-washed test tubes; after clot separation, serum was stored at -18°C. The duplicate determinations were performed using the flame technique of atomic absorption spectrophotometry (12). Height, wt, BMI, and ST were used as anthropometric variables.…”
Section: Bmi Body Mass Indexmentioning
confidence: 99%
“…Zn is reported to play an important role in the maintenance of membrane structure and function (Bettger & O'Dell, 1981), and to alter the permeability of major ions, contractile force and transmembrane potential in the muscle cells (Muneoka et al 1979). Since Zn is needed in wound healing, and atherosclerosis is believed to begin with mini-trauma in the intima of vessels, a low Zn concentration may result in inadequate repair (Vuori et al 1985). It has been shown that Zn levels of the necrotic area in men who died of myocardial infarction are low (Speich, 1982).…”
Section: Discussionmentioning
confidence: 99%